2022
DOI: 10.15252/embj.2021109256
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome slowdown triggers codon‐mediated mRNA decay independently of ribosome quality control

Abstract: The control of mRNA stability plays a central role in regulating gene expression patterns. Recent studies have revealed that codon composition in the open reading frame determines mRNA stability in multiple organisms. Based on genome‐wide correlation approaches, this previously unrecognized role for the genetic code is attributable to the kinetics of the codon‐decoding process by the ribosome. However, complementary experimental analyses are required to clarify the codon effects on mRNA stability and the relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 78 publications
4
56
0
Order By: Relevance
“…In agreement with no significant correlation between the stability of the injected mRNA and codon adaptation index (Supplemental Fig. 2 B), a recent work showed that codon optimality is a better predictor of mRNA stability than codon usage in zebrafish 46 . Therefore, iCodon provides a practical first step toward more targeted solutions.…”
Section: Discussionsupporting
confidence: 85%
“…In agreement with no significant correlation between the stability of the injected mRNA and codon adaptation index (Supplemental Fig. 2 B), a recent work showed that codon optimality is a better predictor of mRNA stability than codon usage in zebrafish 46 . Therefore, iCodon provides a practical first step toward more targeted solutions.…”
Section: Discussionsupporting
confidence: 85%
“…The factors that are reported to bind to these states all have the potential to repress translation initiation. For instance, in yeast, Not5p binds the empty E-site and helps recruit deadenylation machinery; given the link between deadenylation and translational repression, it could be that Not5p (CNOT3, in humans) also represses translation initiation (Buschauer et al, 2020, Veltri et al, 2021, Mishima et al, 2022). An alternative is the recruitment of EDF1/GIGYF2/4EHP, which are known to recognize collided ribosomes as part of the RQC pathway and repress translation initiation on those substrates (Brandman, O., and Hegde, 2016, Hickey et al, 2020, Juszkiewicz et al, 2020, Sinha et al, 2020, Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent work has shown that slow elongation, specifically through nonoptimal codon usage and slow decoding, triggers mRNA decay by a mechanism distinct from the RQC pathway (Buschauer et al, 2020, Veltri et al, 2021, Mishima et al, 2022). Best described in yeast, this pathway is mediated by the CCR4-NOT deadenylase complex (Presnyak et al, 2015, Hanson et al, 2018, Buschauer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotes, mRNAs with sub-optimal codons are subjected to a specialized "codon-optimality decay" pathway (2,3) and codon usage is a major determinant of mRNA half-life (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Interestingly, slow translation and thus low codon-optimality may be sensed directly by the conserved multi-functional cytoplasmic deadenylase CCR4-NOT (14,15).…”
Section: Introductionmentioning
confidence: 99%